2017
DOI: 10.1139/cjm-2016-0449
|View full text |Cite
|
Sign up to set email alerts
|

Diversity ofBacillus-like bacterial community in the sediments of the Bamenwan mangrove wetland in Hainan, China

Abstract: Members of the genus Bacillus and related spore-forming genera are ubiquitous. However, Bacillus-like species isolated from marine sediments have attracted less interest than their terrestrial relatives. Here, we investigated the diversity of Bacillus-like bacterial communities in the sediments of the Bamenwan mangrove wetland in Hainan, China, using culture-dependent and culture-independent methods, and present the first report on this subject. We also discovered some potential novel species from the sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
(16 reference statements)
4
9
0
Order By: Relevance
“…The results of the present study revealed low but significant genetic differentiation in U. hordei isolates with a similarity coefficient of over 60%. Parallel to these findings, Xu et al (2004) also documented the phenomenon of diverse geographical origin of U. scitaminea population with small values of dissimilarity coefficients (Owati et al, 2019). The low level of genetic differentiation and formation of two distinct sub-groups within U. hordei isolates of PZ reflected an extreme event of genetic discrimination that happened at a small scale, probably due to migration.…”
Section: Discussionsupporting
confidence: 58%
“…The results of the present study revealed low but significant genetic differentiation in U. hordei isolates with a similarity coefficient of over 60%. Parallel to these findings, Xu et al (2004) also documented the phenomenon of diverse geographical origin of U. scitaminea population with small values of dissimilarity coefficients (Owati et al, 2019). The low level of genetic differentiation and formation of two distinct sub-groups within U. hordei isolates of PZ reflected an extreme event of genetic discrimination that happened at a small scale, probably due to migration.…”
Section: Discussionsupporting
confidence: 58%
“…The traditional way to analyze the diversity of Bacillus -like bacteria is based on bacterial strain isolation and 16S rRNA gene identification (Maughan and Van der Auwera, 2011; Dheemana et al, 2017; Panosyan et al, 2018). Recently, the use of HTS surveying of Bacillus -like bacteria directly in soils and combining it with a one-by-one isolation method was also reported (Liu et al, 2017; Mukhtar et al, 2018). Those studies showed that more Bacillus -like bacterial genera were detected by HTS than by the culture-dependent method, which indicated that HTS was a more effective way to discover specific microbial diversity (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given that most of Bacillus -like bacteria are cultivable (Seldin et al, 1998; McSpadden Gardener, 2014), and most of studies investigating the distribution of Bacillus -like bacteria in soils are based on the isolation method, and the isolated strains were identified by 16S rRNA gene sequencing one by one (Liu et al, 2016, 2017; Mukhtar et al, 2018). This protocol is a laborious and time-consuming, which restricts us to investigate the diversity of Bacillus -like bacteria with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In saline environments, members of the phylum Firmicutes, e.g., Bacillus, Virgibacillus, Halobacillus, Oceanobacillus, Paenibacillus and Brevibacillus have found to be more abundant as compared to other bacteria (Liszka et al 2012). Halophilic Bacilli have a wide range of applications in bioenzyme production, biodefense, biofuel production and bioremediation of organic toxic compounds (Lundberg et al 2012;Liu et al 2017). These Bacilli are a good source of novel enzymes that function under salt stress conditions, such as proteases, xylanases, cellulases and amylases with polyextremophilic properties (Taprig et al 2013).…”
Section: Introductionmentioning
confidence: 99%